Corrosion and tribocorrosion behaviour of beta-type Ti-Nb and Ti-Mo surfaces designed by diffusion treatments for biomedical applications - Urena, J. (2018)
Corrosion and tribocorrosion behaviour of modified Ti surfaces through thermochemical treatments has been studied. Electrochemical Impedance Spectroscopy (EIS) and reciprocating sliding tests using a ball-on-plate tribometer under 1 N load and alumina as counter-material were used to evaluate the influence of Nb and Mo on titanium corrosion and tribocorrosion properties.Ti-Nb and Ti-Mo surfaces exhibited better anticorrosive properties than CP-titanium. Under tribological action the modified Ti surfaces showed similar coefficient of friction and lower tendency to corrosion compared to CP-Ti. Furthermore, Nb diffusion increased the repassivation rate with respect to Ti and Ti-Mo surfaces due to its stable passive film.